Supply chain risks in humanitarian relief operations: a case of Cyclone Idai relief efforts in Zimbabwe - Felix Chari; Bethuel Sibongiseni Ngcamu; Cawe Novukela (Journal of Humanitarian Logistics and Supply Chain Management, 2021)
Purpose – The rising threat of tropical cyclones in Zimbabwe is of great importance in establishing the general sources of humanitarian supply chain risks and assessing their negative impact on relief operations. There is a scarcity of studies that collate such evidence toward enhanced humanitarian supply chains in Southern Africa. With this in mind, this study explored scattered evidence on supply chain risks in the delivery of humanitarian aid to victims of Cyclone Idai in Zimbabwe. Design/methodology/approach – This reflective study evaluates supply chain risks associated with Cyclone Idai humanitarian relief operations through qualitative in-depth interviews with relevant actors in the field. The data were triangulated with secondary information from associated publications, blogs and newspapers to reflect the truth about the phenomena under investigation. Findings – The results show that Cyclone Idai disaster response operations were adversely affected by social, economic and political/governmental risk factors. In the same breath, poor or inadequate infrastructure and environmental factors were also contributing factors toward the futility of humanitarian relief operations. Practical implications – This study is significant as it endeavors to contribute toward humanitarian supply chain management, specifically in assisting humanitarian organizations with suggested strategies that would work toward making humanitarian relief supply chains more resilient. However, more research needs to be done toward optimized implementation strategies for the suggested framework. Originality/value – It is to the best knowledge of these researchers that this is a unique study carried out to examine humanitarian supply chain risk factors in Cyclone Idai relief operations in Zimbabwe.